2017
DOI: 10.1007/978-3-319-51541-0_151
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Carbon Build-Up on the Flue Wall of Anode Baking Furnace

Abstract: A hard carbon build-up layer often forms on the flue wall surface in anode baking furnaces. The layer accumulates over thermal circles and needs to be mechanically removed regularly to ensure sufficient space for the anodes between flue walls. The underlying mechanisms are still unknown and the extent of the carbon build-up varies from plant to plant. The build-up on the flue wall, taken from an autopsy of an open top furnace, has been examined. Microstructure and phase compositions of the carbon build-up, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…The preliminary study confirmed the presence of carbon in the outer layers facing the anode pit, with a significant reduction in carbon level farther into the lining . This corresponds to investigations on similar samples showing carbon build‐up on the flue wall . The overall stability of the flue wall during thermal cycling is maintained by the use of mortar‐filled gaps in the wall.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The preliminary study confirmed the presence of carbon in the outer layers facing the anode pit, with a significant reduction in carbon level farther into the lining . This corresponds to investigations on similar samples showing carbon build‐up on the flue wall . The overall stability of the flue wall during thermal cycling is maintained by the use of mortar‐filled gaps in the wall.…”
Section: Discussionsupporting
confidence: 76%
“…At higher flue wall temperatures, parts of the hydrocarbons are likely to crack at the refractory surface, especially in areas with low suction, leaving solid carbon at the surface and in the open porosity, and consequently increased density. The reduction in density after heat treatment in air confirmed oxidation of carbon, hence supporting the proposed carbon cracking reaction . The preliminary study confirmed the presence of carbon in the outer layers facing the anode pit, with a significant reduction in carbon level farther into the lining .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Next, there were some white spots scattered around the surface of each magnetized sample. The white spot was believed to act as the silica particles and MAC_B2III contained more white spots because of the addition of D350 chemical that were contained in silica particles (Wang, et al, 2017). X-Ray Diffraction (XRD).…”
Section: Characterization Of Magnetic Activated Carbonmentioning
confidence: 99%